HUBUNGAN BUDAYA ORGANISASI TERHADAP MUTU ASUHAN KEPERAWATAN - Muhith, Abdul; rizqina, Rachma; Zulailah, Diah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2019)
Hospitals as health care institutions need to improve their skills, speed, ease and accuracy in performing nursing practice. The right organizational culture can easily direct and focus on improving the quality of nursing care. The purpose of this study to analyze the relationship of organizational culture with the quality of nursing care in RSI Sawatah Mojokerto Inpatient Room.This research used cross sectional approach. The population in this study were all nurses in RSI Sawatah Mojokerto Inpatient Room with the number of samples of 85 nurses with total sample technique. Measurers in this study used OCAI for Organizational culture and quality questionnaire of nursing care. Statistical analysis used was Spearman Rank test.The result of analysis was found that almost half of the nurses in SSI inpatient unit of RSI Sakinah Mojokerto embraced Hierarchy Organization Culture as many as 29 respondents (34.1%) and for Good Nursing Standards were 66 respondents (77.6%) while High Professional Performance Standards, was as many as 66 respondents (77.6%). Spearman test analysis results obtained significance value (p) = 0.018 which explains that there was Organizational Culture Relation with Nursing Care Quality in Inpatient Room RSI Sakinah Mojokerto. Hospitals as a place of health services should be able to develop appropriate organizational culture and improve the quality of nursing care through training, research, supervision, and other methods that are effective and efficient. Keywords: Nursing Care; Organizational Culture; Quality; Nurse.